Spanish reader of South American history (1917)
The purpose of this book is to help supply the need of suitable classroom texts dealing with South America. The increasing interest of this country in the republics of the southern continent is already manifest among the students in our schools and colleges, whose eagerness to learn Spanish is due largely to their desire to learn about South America.